Analiza fundamentalna - produkt czy opakowanie? - Mikołajewicz, Grzegorz (Fundamental Analysis - Product Or Packaging?, 2005)
The article is an attempt to answer the question of whether the fundamental analysis allows to estimate the real, objective value of a company or whether its outcome would rather reflect the expectations of the customer. Moreover, it was stated that the process of valuation is very subjective and that one should not expect to get the only true value, but rather a set of possible company values.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 258-267